ST-Segment Recovery and Outcome After Primary Percutaneous Coronary Intervention for ST-Elevation Myocardial Infarction: Insights From the Assessment of Pexelizumab in Acute Myocardial Infarction (APEX-AMI) Trial - Buller, Christopher E.; Fu, Yuling; Mahaffey, Kenneth W.; Todaro, Thomas G.; Adams, Peter; Westerhout, Cynthia M.; White, Harvey D.; van 't Hof, Arnoud W.J.; Van de Werf, Frans J.; Wagner, Galen S.; Granger, Christopher B.; Armstrong, Paul W. (Circulation (New York, N.Y.), 2008)
Background— Primary percutaneous coronary angioplasty is an effective and widely adopted treatment for acute myocardial infarction. A simple method of determining prognosis after primary percutaneous coronary intervention (PCI) would facilitate appropriate care and expedite hospital discharge. Thus, we determined the prognostic importance of various measures of ST-segment–elevation recovery after primary PCI in a large, contemporary cohort of patients with ST-elevation myocardial infarction. Methods and Results— We analyzed ECG data describing the magnitude and extent of ST-segment elevation and deviation before and early after (ie, 30 minutes) primary PCI in the study cohort of 4866 subjects with electrocardiographically high-risk ST-elevation myocardial infarction enrolled in the Assessment of PEXelizumab in Acute Myocardial Infarction (APEX-AMI) trial. Associations among 6 methods for calculating ST-segment recovery, biomarker estimates of infarct size (ie, peak creatine kinase, creatine kinase-MB, and troponin I and T), and prespecified clinical outcomes (ie, rates of 90-day death and 90-day death, heart failure, or shock) were examined. All ST-segment–recovery methods provided strong prognostic information regarding clinical outcomes. A simple ST-segment–recovery method of residual ST-segment elevation measurement in the most affected lead on the post-PCI ECG performed as well as complex methods that required comparison of pre- and post-PCI ECGs or calculation of summed ST-segment deviation in multiple leads (ie, worst-lead residual ST elevation: adjusted hazard ratio for 90-day death rate [reference <1 mm]: 1 to <2 mm, 1.23 [95% CI 0.74 to 2.03]; ≥2 mm, 2.22 [95% CI 1.35 to 3.65], corrected c-index=0.832; 90-day death/congestive heart failure/shock [reference <1 mm]: 1 to <2 mm, 1.55 [95% CI 1.06 to 2.26]; ≥2 mm, 2.33 [95% CI 1.59 to 3.41], corrected c-index=0.802). Biomarker estimates of infarct size declined in association with enhanced ST-segment recovery. Conclusions— An ECG performed early after primary PCI is a simple, widely available, inexpensive, and powerful prognostic tool applicable to patients with ST-elevation myocardial infarction.